Wage inequality during the long-term stagnation in Japan: Changes within and between establishments - Mika Akesaka; Koyo Miyoshi (Osaka University, Institute of Social and Economic Research (ISER), 2018)
Wage inequality between individuals has changed little in Japan in recent times unlike in other developed countries. We examine changes in wage inequality within and between establishments during the prolonged stagnation period in Japan. Using a micro-level worker-establishment dataset from 1991 to 2012, we find changes in inequality during the 1990s. First, an increase in the variance in the establishment fixed effects expanded men's between-establishment inequality. Meanwhile, a reduction of returns to tenure decreased men's within-establishment inequality and thus suppressed rising individual wage inequality. Second, we find a different trend in women's wage inequality. Between-establishment inequality was larger than that of men in the early 1990s. However, since the structure of wage inequality in men changed significantly, the composition of inequality between men and women has become similar in recent years. Finally, the assortativeness between workers and establishment rose for both sexes.
Keywords: J21; J31; M52; 330; inequality trends; returns to tenure; within- and between-establishment inequality